Copper‐Catalyzed Enantioselective Doyle–Kirmse Reaction of Azide‐Ynamides via α‐Imino Copper Carbenes - Liu, Xin; Liu, Li‐Gao; Chen, Can‐Ming; Li, Xiao; Xu, Zhou; Lu, Xin; Zhou, Bo; Ye, Long‐Wu (Angewandte Chemie International Edition, 2023)
[2,3]‐Sigmatropic rearrangement reaction involving sulfonium ylide (Doyle–Kirmse reaction) generated from metal carbenes represents one of the powerful methods for the construction of C(sp3)−S and C−C bonds. Although significant advances have been achieved, the asymmetric versions via the generation of sulfonium ylides from metal carbenes have been rarely reported to date, and they have so far been limited to diazo compounds as metal carbene precursors. Here, we describe a copper‐catalyzed enantioselective Doyle–Kirmse reaction via azide‐ynamide cyclization, leading to the practical and divergent assembly of an array of chiral [1,4]thiazino[3,2‐b]indoles bearing a quaternary carbon stereocenter in generally moderate to excellent yields and excellent enantioselectivities. Importantly, this protocol represents a unique catalytic asymmetric Doyle–Kirmse reaction via a non‐diazo approach and an unprecedented asymmetric [2,3]‐sigmatropic rearrangement via α‐imino metal carbenes. A novel copper‐catalyzed asymmetric Doyle‐Kirmse of azide‐ynamides via α‐imino copper carbenes is disclosed, enabling the practical and divergent assembly of chiral [1,4]thiazino [3,2‐b]indoles in generally moderate to excellent yields and excellent enantioselectivities. This protocol represents the first asymmetric Doyle–Kirmse reaction via a non‐diazo approach and the first asymmetric [2,3]‐sigmatropic rearrangement via α‐imino metal carbenes.